Does the Islamic marketing mix model matter in coping with the rising cost of living in Malaysia during the crisis? / Mohammad Tahir Zainuddin … [et al.] - Zainuddin, Mohammad Tahir; Nazri, Muhamad Azrin; Mohd Dali, Nuradli Ridzwan Shah; Ahmad, Nursilah (2023)
The objective of this study was to enhance the current understanding and bridge the gaps in the existing literature by examining the factors that could remedy the impact of the rising cost-of living issue that widely affected people in Malaysia recently. Using the Islamic Marketing mix model consisting of Islamic Product, Islamic Promotion, Islamic Price, Islamic Place (distribution), and Islamic People in Malaysia, the analysis is based on data obtained from a survey conducted across Malaysia involving 304 valid respondents of Malaysian citizens aged between 19 and above. The objectives of the study were to stabilize the impact of the rising cost of living. The Structural Equation Models (SEM) statistical results reveal that four components research hypothesis, namely product, price, promotion, and people have a significant impact on remedying the rising cost of living. The research was made based on cross-sectional data in Malaysia; thus, a generalization of results for application in other countries may be limited. The findings of this study are significantly important to provide input for the authorities in enhancing relevant policies to improve the well-being of the people in Malaysia. The framework of this study was originally developed and tested during the health and economic crisis hits Malaysia.